Micropropagation of annatto (Bixa orellana L.) from mature tree and assessment of genetic fidelity of micropropagated plants with RAPD markers - Siril, E. A. (Springer-Verlag, 2012)
An in vitro propagation technique based on axillary bud proliferation was developed for the first time to mature annatto (Bixa orellana L.) tree. Nodal segments cultured on Murashige and Skoog (MS) medium supplemented with 1.0 μM benzyl adenine (BA) and tender coconut water (10 %) showed significantly high (P < 0.05) explant response (67.0 %), development of elongated shoots (3.36), shoot buds (8.9) and shoot elongation (3.53 cm). Cytokinins like zeatin, isopentenyl adenine (2-iP), kinetin, or thidiazuron (TDZ) were inferior to BA to induce multiple shoots. Seasonal variations significantly affected the in vitro response of nodal explants. In vitro rooting experiments have showed 55.6 % rooting on MS medium containing 15 μM indole-3-butyric acid (IBA). Alternatively, in vitro raised shoots were rooted (61.1 %) ex vitro, by 10 mM indole-3-butyric acid (IBA) for 30 s. The results of the RAPD marker system revealed the genetic stability among the micropropagated plants. The present protocol in brief, can be used for the clonal propagation of the superior genotype and preservation of germplasm.